Response of soft rock and sand compound soil structure to freeze-thaw cycles in Mu Us Sandy Land, China - Zhang, Haiou; Cao, Tingting; Guo, Zhen; Wang, Yingguo; Hou, Xiandong (Frontiers in Environmental Science, 2024)
In order to accurately understand the relationship between soil structure and climate feedback in the frozen soil area of Mu Us Sandy Land, China, and to explore the key control factors for the structural stability of soft rock and sand compound soil under freeze-thaw environment, the indoor freeze-thaw simulation experiment was applied. The results show that the freeze-thaw period, clay content, organic matter and their interactions have significant effects on the stability of composite soil aggregates. After 10 freeze-thaw cycles, the aggregate content in the 1:0, 1:1, 1:2, and 1:5 composite soil with a diameter greater than 1 mm decreased by 55%, 34%, 44%, and 57%, while the aggregate content with a diameter less than 1 mm increased by 91%, 70%, 66%, and 87%, and the aggregate composition of each particle size is mainly concentrated in the range of 0.25–0.5 mm. Under freeze-thaw conditions, the changes of clay and aggregate content in different proportions of composite soil is the same, all showing 1:1>1:2:>1:5, and 1:1 composite soil with >0.25 mm aggregate content is the highest. Under freeze-thaw alternations, 1:1, 1:2 and 1:5 composite soil aggregates (<0.5 mm) showed a significant positive correlation with soil organic matter, while there is no significant correlation between large aggregates (>1 mm) and soil organic matter. In conclusion, the freeze-thaw cycle reduces the structural stability of composite soil aggregates, and clay are the key controlling factors for the formation and structural stability of composite soil aggregates.